2019
DOI: 10.1002/jbm.a.36857
|View full text |Cite
|
Sign up to set email alerts
|

A BMSCs‐laden quercetin/duck's feet collagen/hydroxyapatite sponge for enhanced bone regeneration

Abstract: Treating critical-sized bone defects is an important issue in the field of tissue engineering and bone regeneration. From the various biomaterials for bone regeneration, collagen is an important and widely used biomaterial in biomedical applications, hence, it has numerous attractive properties including biocompatibility, hyper elastic behavior, prominent mechanical properties, support cell adhesion, proliferation, and biodegradability. In the present study, collagen was extracted from duck's feet (DC) as a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 54 publications
3
22
0
1
Order By: Relevance
“…A subsequent study explored the effects of quercetin/duck's foot collagen/hydroxyapatite sponge on calvarial bone defects. Similar outcomes were found, with increased BMD, BV and new bone formation 8 weeks after surgery [48]. In another study, parietal bone defects in New Zealand rabbits were grafted with quercetin solution mixed with collagen matrix for 14 days and bone histological assessment was performed to quantify new bone formation.…”
Section: Type Of Animalsupporting
confidence: 59%
See 2 more Smart Citations
“…A subsequent study explored the effects of quercetin/duck's foot collagen/hydroxyapatite sponge on calvarial bone defects. Similar outcomes were found, with increased BMD, BV and new bone formation 8 weeks after surgery [48]. In another study, parietal bone defects in New Zealand rabbits were grafted with quercetin solution mixed with collagen matrix for 14 days and bone histological assessment was performed to quantify new bone formation.…”
Section: Type Of Animalsupporting
confidence: 59%
“…Biodegradable poly(lactic-co-glycolic acid)-based microspheres loaded with 1 µg/mL quercetin raised ALP, COL1 and Runx-2 expression in stem-cell spheroids cultured in osteogenic medium [72]. Song and co-authors found that two types of three-dimensional bone scaffold (quercetin/silk fibroin/hydroxyapatite scaffold and quercetin/duck's foot collagen/hydroxyapatite sponge) enhanced osteogenesis, determined by increases in MSCs' growth and proliferation, ALP, COL1, osteocalcin and Runx-2 [47,48]. Tripathi et al (2015) seeded murine MC3T3-E1 cells onto calcium-deficient hydroxyapatite scaffolds with quercetin and found elevations of osteoblast number, ALP, Runx-2, COL1, BSP, osteocalcin and calcium mineralisation [68].…”
Section: The Effects Of Quercetin On Osteoblastogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…100 µl reagents have finally been carefully distributed to 96- well plates. The optics densities were tested with a microplate reader at 570 nm ( Song et al, 2019 ).…”
Section: Characterization Of Minerals Doped Hydroxyapatite and Biocommentioning
confidence: 99%
“…When it is appraised about medical devices, medication equipments, and cutting tools etc, tungsten has found its place in our daily lives. However, with the view of many unique properties and advantages, there are some limitations have also been imposed with regard to vulnerability of air sourced tungsten dust to safeguard mine workers and the persons involved in processing of metals ( Song et al, 2019 ). There are very few agencies, which also set limits on water-soluble compounds where tungsten was the essential element to address the broader section of the community at the risk of exposure.…”
Section: Introductionmentioning
confidence: 99%